2021
DOI: 10.3988/jcn.2021.17.3.443
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Patients with Persistent Apogeotropic and Persistent Geotropic Direction-Changing Positional Nystagmus

Abstract: Background and Purpose This study aimed to determine the clinical features, diagnosis, and treatment of patients with persistent geotropic (pG) and persistent apogeotropic (pAG) direction-changing positional nystagmus (DCPN). Methods This retrospective study included 30 patients with pG-DCPN and 44 patients with pAG-DCPN. All patients underwent neurological and neurotological examinations, including an evaluation of gaze-evoked nystagmus, eye-movement tests, and assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 45 publications
1
9
0
1
Order By: Relevance
“…Others have noted that the nystagmus of cupulolithiasis should be lower velocity than with freely moving particles, which have a mechanical advantage in moving the cupula due to a plunger‐like effect 44,51,65,77 . Case studies of jam show peak velocities exceeding 50 d/s, as high as those found with geotropic/canalithiasis H‐BPPV, 33 and nystagmus velocities as high as 80°/s have been reported, 78 which is not consistent with experimental models of cupulolithiasis in which peak velocities are 1/3 those of canalithiasis 44 …”
Section: Discussionmentioning
confidence: 97%
“…Others have noted that the nystagmus of cupulolithiasis should be lower velocity than with freely moving particles, which have a mechanical advantage in moving the cupula due to a plunger‐like effect 44,51,65,77 . Case studies of jam show peak velocities exceeding 50 d/s, as high as those found with geotropic/canalithiasis H‐BPPV, 33 and nystagmus velocities as high as 80°/s have been reported, 78 which is not consistent with experimental models of cupulolithiasis in which peak velocities are 1/3 those of canalithiasis 44 …”
Section: Discussionmentioning
confidence: 97%
“…Авторы исследования полагают, что рецидивирующее ДППГ может быть манифестацией мигрени со стороны внутреннего уха -«отомигрени», включающей кохлеарные, вестибулярные и кохлеовестибулярные симптомы [34]. Наконец, показано, что персистирующий геотропный меняющий направление позиционный нистагм ассоциирован с аутоиммунными заболеваниями и анамнезом мигрени [35]. В отношении взаимосвязи ВМ и ДППГ интересны данные о частом выявлении дефицита 25-гидроксивитамина D в плазме крови у пациентов с ВМ [36].…”
Section: л е к ц и яunclassified
“…Moreover, spontaneous nystagmus is believed to stem from the upward deflection of the cupula, causing it to beat toward the unaffected side ( 8 , 15 ). In the bow and lean test (BLT), 83–100% of patients with light cupula present with bow nystagmus and/or lean nystagmus ( 4 , 9 , 16 ). The fast phase direction of bow nystagmus corresponds to the affected side of the light cupula ( 4 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the bow and lean test (BLT), 83–100% of patients with light cupula present with bow nystagmus and/or lean nystagmus ( 4 , 9 , 16 ). The fast phase direction of bow nystagmus corresponds to the affected side of the light cupula ( 4 , 9 ). However, lean nystagmus is the opposite of bow nystagmus ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation